Clinical Analysis of Acinar Cell Carcinoma of the Pancreas: A Single-Center Experience of 45 Consecutive Cases. (28th October 2020) - Zhou, Wentao; Han, Xu; Fang, Yuan; Han, Siyang; Cai, Yumeng; Kuang, Tiantao; Lou, Wenhui; Wang, Dansong
Backgrounds: Acinar cell carcinoma of the pancreas is a rare malignancy, and its features remain unclear. We aimed to analyze the clinical characteristics, treatment and prognosis of acinar cell carcinoma with our institutional case series. Methods: Patients diagnosed with acinar cell carcinoma in our hospital between 2005 and 2019 were reviewed. Investigations on clinicopathological features, treatment details and long-term survival were performed. Results: A total of 45 pathologically confirmed acinar cell carcinomas were identified. The median age at diagnosis was 58 years with a male-to-female ratio of 3.1:1. There were 24 (53.3%) localized, 5 (11.1%) locally advanced and 16 (35.6%) metastatic cases, with a pancreatic head-to-body/tail ratio of 1:1.4 for all the primary lesions. In the localized group, there were 10 pancreatoduodenectomy, 12 distal pancreatectomy, 1 total pancreatectomy, and 1 distal pancreatectomy combined with proximal gastrectomy. Among the locally advanced and metastatic cases, 13 patients received chemotherapy, 1 received concurrent radiochemotherapy, 1 underwent synchronous resection of primary tumor and liver metastasis, 1 underwent palliative operation, 1 underwent exploratory laparotomy, and 4 required no treatment. The median overall survival of this series was 18.9 months with a 5-year survival rate of 19.6%. Moreover, the resected acinar cell carcinoma patients were associated with prolonged survival compared with the unresected cases (36.6 vs. 8.5 months, P < 0.001). Conclusions: Surgical resection could improve the long-term survival of acinar cell carcinoma patients, which might also improve the prognosis of selected metastatic cases. Large-scale studies are needed to further clarify the biological behavior and clinical features, and to seek the optimal treatments.